INFINITy : A fast machine learning-based application for human influenza A and B virus subtyping - Cacciabue, Marco Polo Domingo; Marcone, Débora Natalia (Wiley, 2023)
Influenza viruses are one of the main agents causing acute respiratory infections (ARI) in humans resulting in a large amount of illness and death globally.1, 2 The influenza viruses classification is based on the nomenclature proposed by the World Health Organization (WHO)3 that is widely accepted and used by the medical and scientific communities throughout the world. Since the pandemic in 2009, two subtypes of human influenza A viruses, A(H1N1)pdm09 and A(H3N2), and two lineages of influenza B, B/Victoria and B/Yamagata, have been responsible for the vast majority of cases each year. Within each subtype and lineage, different clades and genetic groups were described to reflect the continuous viral evolution, driven by antigenic drift. The WHO Global Influenza Surveillance and Response System (GISRS) studies human influenza viruses from >110 countries, to monitor circulating strains, understand epidemiology and evolution, and contribute to verify the vaccine effectiveness and update its formulation each year.4, 5 A growing number of laboratories and research centers is contributing to this initiative by sequencing the whole viral genome or the hemagglutinin (HA) gene from local strains.